2008
DOI: 10.1002/acp.1472
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal belief and susceptibility to the conjunction fallacy

Abstract: Numerous studies have shown paranormal believers misperceive randomness and are poor at judging probability. Despite the obvious relevance to many types of alleged paranormal phenomena, no one has examined whether believers are more susceptible to the 'conjunction fallacy'; that is to misperceiving co-occurring (conjunct) events as being more likely than singular (constituent) events alone. The present study examines believer vs. non-believer differences in conjunction errors for both paranormal and non-parano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
123
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(155 citation statements)
references
References 50 publications
27
123
5
Order By: Relevance
“…In general, this research on psychic beliefs is consistent with studies linking other kinds of paranormal beliefs to less analytic or critical thinking (see Gervais & Norenzayan, 2012;Pennycook, Cheryne, Sleli, Koehler, & Fugelsang, 2012), including less critical evaluation of hypothetical arguments (Stanovich & West, 1998;Svedholm & Lindeman, 2012) or an increased likelihood of endorsing conspiracy theories that most people reject based on careful scrutiny of the evidence (Bruder, Haffke, Neave, Nouripanah, & Imhoff, 2013;Lobato, Mendoza, Sims, & Chin, 2014). Although group differences in analytical thinking and logic tasks have not always been observed (compare Dagnall, Drinkwater, Parker, & Rowley, 2014, to Rogers, Davis, & Fisk, 2009, these represent some of the most reliable cognitive difference between paranormal believers and skeptics observed to date.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In general, this research on psychic beliefs is consistent with studies linking other kinds of paranormal beliefs to less analytic or critical thinking (see Gervais & Norenzayan, 2012;Pennycook, Cheryne, Sleli, Koehler, & Fugelsang, 2012), including less critical evaluation of hypothetical arguments (Stanovich & West, 1998;Svedholm & Lindeman, 2012) or an increased likelihood of endorsing conspiracy theories that most people reject based on careful scrutiny of the evidence (Bruder, Haffke, Neave, Nouripanah, & Imhoff, 2013;Lobato, Mendoza, Sims, & Chin, 2014). Although group differences in analytical thinking and logic tasks have not always been observed (compare Dagnall, Drinkwater, Parker, & Rowley, 2014, to Rogers, Davis, & Fisk, 2009, these represent some of the most reliable cognitive difference between paranormal believers and skeptics observed to date.…”
supporting
confidence: 57%
“…Krummenacher, Mohr, Haker, & Brugger, 2010;Rogers et al, 2009;Watt & Wiseman, 2002). Overall we found evidence that skeptics outperformed believers on four measures that require some form of analytical thinking: (1) the logic subscale of the Shipley Institute of Learning Scale, which required them to complete patterns of words, letters, and numbers; (2) the remote associations task, which required the identification of a nonpresented word that was related to three presented words; (3) the rejection of conspiracies on the conspiracy questionnaire, suggesting that skeptics engage in more critical or analytical thinking about these kinds of conspiracies than do believers; and (4) the argument evaluation task, which requires critical thinking about the quality of arguments made during a hypothetical debate.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, paranormal believers were just as prone to making conjunction errors as non-believers. Rogers, Davis, and Fisk (2009) have since criticised this study on several grounds. Firstly, it sampled psychology undergraduates who are likely to have some knowledge of probability theory.…”
Section: Paranormal Belief and The Conjunction Fallacymentioning
confidence: 99%
“…Finally, it utilised a single conjunction event which had little relevance to ostensibly paranormal phenomena. In response, Rogers et al (2009) examined paranormal believers' susceptibility to the conjunction fallacy by creating a series of 16 brief conjunction vignettes incorporating either an ostensibly paranormal or a non-paranormal event. In each case, participants were asked to estimate the likelihood of each component and their conjunction occurring.…”
Section: Paranormal Belief and The Conjunction Fallacymentioning
confidence: 99%
“…Interestingly, in the same study it was found that the tendency to avoid semantically related guesses was associated to a stronger belief in extrasensory perception. Finally, it has been reported that paranormal believers show fallacies in probabilistic reasoning task and tend to underestimate the likelihood of chance events (Rogers et al 2009). In addition, paranormal believers are more prone to reporting frequent experiences of coincidence during their life (Bressan 2002).…”
Section: Individual Differences and Precisionmentioning
confidence: 99%